Problematika Orangtua Dalam Mendidik Anak di Masa Pandemi Covid-19 - Aan Aprilia; Ahmad Riyadi; Wiwi Uswatiyah (Fakultas Syariah IAIN Laa Roiba Bogor, 2021)
Home study led to a disintegration of the covid-19 spreading chain. In applying home learning systems, parents play a vital role in the student learning process during the current long-range learning system. So with home learning, it is the parents who become educators at home in place of teachers. This research aims to identify what can be problematic for parents in educating children during the covid-19 pandemic. The study involves a qualitative method that offers research interviews, observation and documentation. Among the problems of parents in educating children in the time of the covid-19, children are often in a changed mood, children are less disciplined, children are bored at home, parents need additional quotas to develop the activities of BDR, of course there is much work to be done in developing good communication to develop a good mood for children especially to carry out remote lessons, Guiding and providing motivation for children to be more disciplined, educating children, varying and innovative indoor activities so that they do not get bored quickly.